Identifikasi Hama Lalat Buah (Diptera: Tephritidae) pada Berbagai Macam Buah-buahan - Helda Syahfari; mujiyanto mujiyanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
The research objective is to determine the type of fruit flies that attack fruit. Fruits used in this research are: mango, papaya, starfruit, stone guava, and water guava. The research was conducted in the pests laboratory of Agricultural Quarantine Class I Balikpapan. This type of research is an exploratory description that describes data that was collected in the field by using the method of rearing hosts (maintenance hosts). Once the fruit fly imago emerges from the fruit, then it is collected and finally identified for further identification. The results showed that from the identification, there are four types of fruit flies that attack fruits, namely: Bactrocera carambolae, Bactrocera albistrigata, Bactrocera cucurbitae, Bactrocera papaya.